Relationship between e-recruitment adoption and good governance practices in Nigerian public sector: An empirical study - Sanusi, Ahmad; Mohamed, Ahmad Martadha (Macrothink Institute, 2012)
The universal quest for good governance forces different countries to adopt e-recruitment as recruiting strategy in hiring their teeming workforce in line with global best practices. As part of public service reform Nigerian government encourage public sector organisations to jettison conventional recruitment method in favour of electronic recruitment for transparency, accessibility and efficiency in recruitment exercises.This study empirically investigates the relationship between e-recruitment adoption and good governance practices in Nigerian public service. The study Modified Technology Acceptance Model (TAM) to analyse the response generated from 326 survey respondents.The findings indicated that e-recruitment adoption is yet to provide good governance.In the overall, this study offer important insight and recommended that government agencies involved should put effective machinery in motion in order to enrich and improve good governance practices in e-recruitment in Nigerian public sector.